Going through the proof of the proposition in the title.

Let $M_1^n, M_2^m$ be differentiable manifolds and let $\varphi : M_1 \to M_2$ be a differentiable mapping. For every $p \in M_1$ and for each $v \in T_p M_1$, choose a differentiable curve $\alpha : (-\epsilon,\epsilon) \to M_1$ with $\alpha(0) = p$, $\alpha'(0) = v$. Take $\beta = \varphi \circ \alpha$. The mapping $d \varphi_p : T_p M_1 \to T_{\varphi(p)} M_2$ given by $d \varphi_p (v) = \beta'(0)$ is a linear mapping that does not depend on the choice of $\alpha$.

There's a very specific bit I can't figure, which I'd like you'd help me to elaborate.

Proof: Let $x : U \to M_1$ and $y : V \to M_2$ be a parameterizations at $p$ and $\varphi(p)$, respectively. Expressing $\varphi$ in these parameterization, we can write $$ y^{-1} \circ \varphi \circ x (q) = (y_1(x_1,\ldots,x_n),\ldots,y_m(x_1,\ldots x_n)) $$ where $$ \begin{array}{l} q = (x_1,\ldots,x_n) \in U \\ (y_1,\ldots,y_m) \in V \end{array}. $$ On the other hand, expressing $\alpha$ in the parameterization $x$, we obtain $$ x^{-1}\circ \alpha(t) = (x_1(t),\ldots,x_n(t)). $$ Therefore, $$ y^{-1} \circ \beta(t) = (y_1(x_1(t),\ldots,x_n(t)),\ldots,y_m(x_1(t),\ldots x_n(t))) $$

Here now the very bit I don't understand

It follows the expression for $\beta'(0)$ with respect to the basis $ \left\{ \left( \frac{\partial}{\partial y_i}\right) _0\right\}$ of $T_{\varphi(p)}M_2$, associated to the parameterization $y$, is given by $$ \beta'(0) = \left(\sum_{i=1}^{n} \frac{\partial y_1}{\partial x_i} x'_i(0), \ldots, \sum_{i=1}^{n} \frac{\partial y_m}{\partial x_i} x'_i(0) \right). $$

The rest of the proof is clear

How exactly is the basis $ \left\{ \left( \frac{\partial}{\partial y_i}\right)_0 \right\}$ used to derive an expression for $\beta'(0)$?


Note that $\beta:(-\epsilon,\epsilon)\to M_2$. So $\beta(0)\in M_2$ and since $M_2$ is of dimension $m$ so $\beta(t) = (y_1(x_1(t),\ldots,x_n(t)),\ldots,y_m(x_1(t),\ldots x_n(t)))....(1)$

Also $\{(\frac{\partial}{\partial y_i})|_t:1\le i\le m\}$ is a basis of the tangent space $T_{\beta(t)}M_2$ at $\varphi(p)=\beta(t)$ for any $t\in(-\epsilon,\epsilon)$.

Now differentiating $(1)$ at $t=0$ we obtain,

$$\beta'(0) = \left(\sum_{i=1}^{n} \frac{\partial y_1}{\partial x_i} x'_i(0), \ldots, \sum_{i=1}^{n} \frac{\partial y_m}{\partial x_i} x'_i(0) \right).$$ With respect to the basis means, $$\beta'(0) = \sum_{i=1}^{n} \frac{\partial y_1}{\partial x_i} x'_i(0)\frac{\partial}{\partial y_1}+ \ldots+\sum_{i=1}^{n} \frac{\partial y_m}{\partial x_i} x'_i(0)\frac{\partial}{\partial y_m} .$$

Hope this works.

  • $\begingroup$ Need some time to digest your answer. $\endgroup$ – user8469759 Mar 21 at 12:06

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.